Kleine-Levin Syndorme: aetiology and pathogenesis, symptoms, diagnosis and treatment - Tuzim, Kamila; Tuzim, Tomasz; Urbańczuk, Magdalena; Urbańczuk, Marcin; Schab, Katarzyna (Journal of Education, Health and Sport, 2018)
AIM: The aim of the study is to present the aetiology, pathogenesis, symptoms, diagnosis and treatment of Kleine-Levin syndrome (KLS). VIEW: Kleine-Levin syndrome is an extremely rare disease entity that consists of attacks of hypersomnia, cognitive and behavioural disorders, hyperphagia and hypersexuality, which are alternated with asymptomatic intervals. The prevalence of this disease, whose etiopathogenesis has not been known yet, all over the world oscillates around 1-5 cases/1,000,000 inhabitants, with predilection for male gender, mainly during the puberty period. Lack of objective diagnostic methods implicates frequent diagnostic errors in KLS. What is more, up to now, an unequivocal position of experts concerning pharmacotherapy of this disease has not been established yet. However, prognosis seems to be favourable as the following episodes become rarer, of weaker intensity up to their complete remission in the majority of patients. CONCLUSION: Further research of aetiology and pharmacological treatment of KLS is needed.